SACRIFICE IN STEPHANIE MEYER’S BREAKING DAWN (2008) - Dewi Christiyani Tumoka; Ceisy N Wuntu; Mister G Maru (English Education Department, 2021)
The purpose of this study is to reveal sacrifice in Meyer’s Breaking down. In conducting the study, the writer delimited this study only in reveling sacrifice in Meyer’s Breaking down. Bella focuses on the main character. The research employs a descriptive qualitative method. It means that all of the data is in the form of words and sentences rather than numbers, and it focuses on the process that produces the results. After analyze the novel the writer may conclude that the kinds of Bella’s sacrifice can be formulated into three categories they are: Willing to stop her study and get married in the very young age, Willing to pregnant event it will endanger her life and the third willing to give up her life for her baby. These three types of sacrifice clearly describe in the novel. Finally, the suggestions are 1) Sacrifice is the very important things in human life, 2) Every relationship needs sacrifice to the sake of others life, 3) Sacrifice is a good moral act that important to become a lesson for everyone.